Clinical researchCaptopril and losartan modify mitogen-induced proliferative response and expression of some differentiation antigents on peripheral blood mononuclear cells in chronic uraemic patients - Bartnicki, Piotr; Majewska, Ewa; Wilk, Radosław; Baj, Zbigniew; Rysz, Jacek (Archives of Medical Science, 2009)
Introduction: The renin-angiotensin system plays an important role in immune mechanisms. It is still insufficiently known whether angiotensin converting enzyme inhibitors and selective angiotensin type 1-receptor antagonists interfere with immune cells. That led us to investigate whether angiotensin converting enzyme inhibitor – captopril and selective angiotensin type 1-receptor antagonist – losartan modify some functions of immune cells in chronic uraemic patients and healthy subjects. Material and methods: In 15 chronic uraemic patients on regular hemodialysis treatment and 15 control subjects we investigated in vitro mitogen induced proliferative response of peripheral blood mononuclear cells and expression of some lymphocyte differentiation antigens in the presence of captopril and losartan, equal to their therapeutic concentrations. As mitogen was used phytohemagglutinin P and phorbol myristate acetate. Results: In our in vitro experiment captopril and losartan, in investigated concentrations, depressed mitogen induced proliferative response of peripheral blood mononuclear cells and lowered expression and numbers of some lymphocyte differentiation antigens in chronic uraemic patients and control subjects. Conclusions: Our in vitro results seem to indicate that captopril and losartan interfere with immune cells and depress some functions of immune cells in chronic uremic patients and healthy subjects. It is very difficult at present to establish significance of these in vitro immunosuppresive effects of captopril and losartan reflects their in vivo action. Its significance for clinical implications necessitates further extensive studies.